The Impact of Calling on Employee Creativity: Evidence From Internet Companies - Lv, Jia; Chen, Wanming; Ruan, Yufang (Frontiers in Psychology, 2021)
With the rapid development of technology and increasingly fierce competition in the global market, innovation has become the most important competitive advantage for enterprises. Employee creativity is widely considered the source of organizational innovation. This study explores the antecedents of employee creativity from the perspective of career development in the context of high-technology industry. Specifically, we examine the effects of calling on employee creativity through the mediation of career commitment and the moderation of responsible leadership. With data collected from a sample of 218 respondents from internet companies, a series of regression analyses was conducted to test the proposed hypotheses. In addition, a moderated mediation model was further examined. Discussion, implications, and limitations are presented.